In the Clouds: On the Vagueness of Atmospheres - Andreas Rauh (Ambiances)
To define ‘atmospheres’ as phenomena between object and subject in the process of perception has almost generally been accepted. Atmospheres are experienced in terms of affect as quasi-objective, free-floating emotions. Given that, how may an atmosphere be described adequately? In the course of listing the multiple characteristics of atmosphere, problems that have to do with language emerge. By juxtaposing the order of language and the order of perception, the vagueness of atmospheres becomes visible – as the sorites paradox (accumulation) shows. Yet descriptions of atmospheres do not have to be vague; they can evoke different characters of atmospheres. The issue of vagueness is discussed from a semantic, ontological and an epistemic perspective. Atmospheres can be made tangible by means of the qualitative-empirical method of ‘aesthetic fieldwork’. This method stresses three methodological aspects as a consequence of the vagueness of atmospheres. It is based on the Parcours commenté and entails a subject-concentrated approach to atmospheres in order to avoid the traps of the forms of vagueness.